Implementation of Learning Evaluation in the 2013 Curriculum - Asdar, Asdar; Marjima, Anisa; Syawal, M.; Kiramang, Khaeruddin (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2023)
Evaluation is a fundamental component in the teaching and learning process, serving as a diagnostic tool to assess the effectiveness of educational activities. This qualitative descriptive study investigates the implementation of learning evaluation aligned with the 2013 Curriculum in Grade X at SMKN 4 Bone, Indonesia. Data were collected through observation, interviews, and documentation involving key educational stakeholders including the principal, vice principal for curriculum, and homeroom teachers. The findings reveal that the evaluation process encompassed key stages: planning, implementation, data processing, and reporting. Notably, SMKN 4 Bone also integrated continuous monitoring and application of evaluation outcomes dimensions that extend beyond conventional evaluation theory. Learning evaluation at this school involved cognitive, affective, and psychomotor domains, assessed through a range of instruments such as written tests, oral assessments, assignments, observations, and performance-based evaluations. While the evaluative procedures largely reflect the theoretical framework, some areas particularly the interpretation and integration of affective and spiritual assessment require further refinement. This study underscores the importance of comprehensive, reflective evaluation systems for curriculum implementation and recommends enhanced teacher capacity-building in evaluation literacy.